Guest Editorial: On Wolverines and Epistemological Totalitarianism - Cardena, Etzel (Journal of Scientific Exploration, 2011)
While strolling with my beloved in the local zoo, we came across a shortish, furry, brown fellow who engaged our sight and seemed to want to play with us, albeit at a distance. He was friendlier even than the acknowledged local clowns (the bears) and surprise followed surprise as we read that this guy belongs to the ferocious wolverine species. Could this same jolly creature be one who would promptly dispatch us, much larger animals, if he were not fed for a while? Thinking about these seemingly contradictory views of one and the same being and of how reality is always more complicated than our models of it, I had the insight that what mostly afflicts "skepticism" is the inability to tolerate complexity and even seemingly contradictory views about a phenomenon. I write "skepticism" in quotation marks to differentiate the epistemological absolutism that pervades both the strident anti- and pro-psi proponents from what I consider a healthy abeyance from fully committing to a closed position in science or other aspects of life. I contend that although the person in a "New Age fair" trading in everything from magical rocks to mysterious odors may seem to be the counterpoint of, say, the arch-skeptic academic who a priori declares psi impossible, they are both afflicted with the same inability to assimilate contradictory information and tolerate ambiguity, and it is only their axioms that differ. And even those may not be that different when we compare superficial materialism and superficial spiritualism (Cardeña, 2010). Consider Humphrey's comments (1995:54) that "materialism is to all intents and purposes the fact of life" no matter how contentious that concept of "matter" is in physics and philosophy (e.g., Wigner, 1969), and that of a Brazilian medium who reported that after death there is food, the same as here, just better-tasting (cf. Playfair, 2010). For both, nothing else seems to exist but everyday objects, the only difference being that for the second they continue after death.